A study of “Chinese-ness” in Eileen Chang’s English novel, The Fall of The Pagoda / Chin Sze Yuin - Chin , Sze Yuin (2019)
A distinct feature in Eileen Chang's authorship is her incorporation of “Chinese-ness” into her English literary works. This is a style she clearly adopts to showcase the traditional Chinese family during the 1930s in Shanghai’s International Settlement. The main aim of this study is to identify the types of “Chinese-ness” that occur in one of Chang's English novels, The Fall of the Pagoda. Additionally, it is also the purpose of this study to look into the effects of “Chinese-ness” on the comprehensibility of readers. A survey was carried out on two different groups of respondents: that is Chinese literates and non-Chinese literates, in order to look into the effects of the incorporation of “Chinese-ness” on the comprehensibility of these two groups of readers. The survey was conducted by using a questionnaire, and the answers gathered were analysed and quantified in percentages to rank the responses of the respondents. It is important to discover how the incorporation of “Chinese-ness” affects the comprehensibility of readers as this has implications for overcoming challenges faced in reading literary writings. This study was carried out with a close textual analysis of the novel, using both quantitative and qualitative approaches.